THE ROLE OF DIGITALIZATION IN PERSONNEL ADMINISTRATION SERVICES AT THE PERSONNEL AND HUMAN RESOURCE DEVELOPMENT AGENCY MAN REGENCY BOLAANG MONGONDOW EAST - Priyono Karsono; Sisca B. Kairupan; Fitri H. Mamonto (PT. Radja Intercontinental Publishing, 2026)
The purpose of this study was to determine the level of digitalization implementation and the determinants in personnel administration services. This study used a descriptive qualitative method with data collection techniques through interviews, observation, and documentation. The results indicate that implementation has been carried out through the use of several applications such as SILAON (Online Personnel Service System) and SIADAB (ASN Digital Attendance Information System). However, this implementation is still partial and not yet fully integrated, resulting in most administrative processes still being carried out manually. Barriers identified include limited technological infrastructure, human resource disparities, and resistance to conventional work cultures. In general, digitalization plays a strategic role in accelerating service processes, improving data accuracy, and achieving transparency and efficiency. The conclusion of this study confirms that although the benefits of digitalization have been felt, strategic and tactical efforts are needed, including infrastructure improvements, enhanced human resource competencies, and system integration, to ensure more optimal and modern personnel services.